On the Bonding Nature in the Crystalline Tri‐Thorium Cluster: Core‐Shell Syngenetic σ‐Aromaticity. (3rd August 2022) - Lin, Xuhui; Mo, Yirong
Abstract: A unique thorium‐thorium bond was observed in the crystalline tri‐thorium cluster [{Th(η 8 ‐C8 H8 )(μ3 ‐Cl)2 }3 {K(THF)2 }2 ]∞, though the claim of σ‐aromaticity for Th3 bond has been questioned. Herein, a new type of core–shell syngenetic bonding model is proposed to describe the stability of this tri‐thorium cluster. The model involves a 3c–2e bond in the Th3 core and a multicentered (ThCl2 )3 charge‐shift bond with 12 electrons scattering along the outer shell. To differentiate the strengths of the 3c–2e bond and the charge‐shift bond, the block‐localized wavefunction (BLW) method which falls into the ab initio valence bond (VB) theory is employed to construct a strictly core/shell localized state and its contributing covalent resonance structure for the Th3 core bond. By comparing with the σ‐aromatic H3 + and nonaromatic Li3 +, the computed resonance energies and extra cyclic resonance energies confirm that this Th3 core bond is truly delocalized and σ‐aromatic. Abstract : A core–shell syngenetic bonding model is proposed to describe the chemical bond in a stable crystalline tri‐thorium cluster. It involves a 3c–2e Th3 core bond and a multicenter (ThCl2 )3 charge‐shift bond with 12 electrons scattering along the outer shell. The resonance energies and extra cyclic resonance energies from the BLW method further confirm that this novel 3c–2e Th3 core bond is delocalized and σ‐aromatic.